Tashmiim ar-Rasaa’il fi Ta’lim al-Lughgah al-Arabiah - Supriyadi, Moh; Nasrullah , Nasrullah (Qismul Arab: Journal of Arabic Education, 2024)
Learning Arabic in the current digital era requires a comprehensive approach, both in terms of learning system design and message design in learning. A well-designed learning system will increase the effectiveness and efficiency of the learning process, while the right message design will help students understand the material more easily. This research aims to determine the message design in learning programs or activities and message design for Arabic language learners using qualitative methodology with the type of library research so that the data obtained can be explained clearly and in detail. The research results in learning, especially teacher Arabic learning, tend to focus on using traditional learning system designs, applying learning theories in design, and the influence of new technology on the design preparation process.